Respiracao bucal: Causas e alteracoes no sistema estomatognatico - Motonaga, S. M.; Berti, L. C.; Anselmo-Lima, W. T. (My University, 2000)
Introduction: The craniofacial growth is determined by many factors, including the genetic inheritance, and chronic oral breathing. Aim: The aim of this research was to clinically evaluate the causes of the chronic mouth breathing and to observe the possible craniodentalfacial complex alterations. Material and method: We analyzed 104 children, ages ranging between three to 10 years. All of them accomplished the otorhinolaryngologic, the stomatognathic system, audiological and roentgenography evaluation. Results: The results showed that the most frequent causes of oral breathing were: allergic rhinitis, pharynx and/or palate tonsils hypertrophy, septal deformities or habit. In our study, the main craniofacial alterations were: open mouth on rest, ogival palate, narrow face with vertical growth predominancy, jaw on lower position and dental malocclusion. Some children presented alterations on the audiological evaluation and a greater number demonstrated alterations on the mastication and swallowing. We didn't observe significant association between the cause of obstruction versus facial features intensity neither between the adenoid obstructive degree versus facial features intensity. Conclusion: These findings allow us to affirm that most of the children who have nasal obstruction and chronic mouth breathing present craniofacial complex alterations.
Mouth breathing: Causes and changes of the stomatognathic system
Keywords: Children; Etiology; Mouth breathing; Nasal obstruction; Stomatognathic system